2017
DOI: 10.1371/journal.pone.0174701
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive bioinformatics analysis of Mycoplasma pneumoniae genomes to investigate underlying population structure and type-specific determinants

Abstract: Mycoplasma pneumoniae is a significant cause of respiratory illness worldwide. Despite a minimal and highly conserved genome, genetic diversity within the species may impact disease. We performed whole genome sequencing (WGS) analysis of 107 M. pneumoniae isolates, including 67 newly sequenced using the Pacific BioSciences RS II and/or Illumina MiSeq sequencing platforms. Comparative genomic analysis of 107 genomes revealed >3,000 single nucleotide polymorphisms (SNPs) in total, including 520 type-specific SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 67 publications
7
25
0
Order By: Relevance
“…The SNP approach is widely used in the study of antimicrobial resistance and genetic diversity and is not limited to M. pneumoniae (26)(27)(28). This study is consistent with previous studies investigating SNPs within M. pneumoniae (20,21). Variant calling against M129 of P1 subtypes showed substantially fewer variants compared to P1 type 2 in both nonsynonymous SNPs and total variants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The SNP approach is widely used in the study of antimicrobial resistance and genetic diversity and is not limited to M. pneumoniae (26)(27)(28). This study is consistent with previous studies investigating SNPs within M. pneumoniae (20,21). Variant calling against M129 of P1 subtypes showed substantially fewer variants compared to P1 type 2 in both nonsynonymous SNPs and total variants.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we did not subgroup based on phylogenetic associations. In the study done by Diaz et al (21), subgroup 'Type 1U' (which authors designated as ubiquitous) was the group containing majority of the P1 subtype 1 isolates. In contrast to their findings, phylogenetic analysis in this study demonstrated that the isolates within the same subgroup type 1U was divided into two large groups.…”
Section: Discussionmentioning
confidence: 99%
“…Watkins et al analyzed five patients with Stevens‐Johnson Sydrome (SJS) infected with Mp and described a unique MLVA type M3‐X‐6‐2 that contributed to the development of SJS. Diaz et al performed whole genome sequencing analysis of 107 M. pneumoniae isolates but did not analyze clinical information. In our previous study, we noted that locus Mpn13 was associated with the P1 genotype .…”
Section: Discussionmentioning
confidence: 99%
“…In China, only 5 ( (32) recently reported that strains with 3 tandem repeats in the Mpn 16 region formed a distinct subgroup named as 1N within the P1 type 1 branch by phylogenetic analysis using the M. pneumoniae core genome. Therefore, the increase in MLVA type 4-5-7-3 may represent the emergence of a new subtype of M. pneumoniae P1 type 1 (32).…”
Section: Discussionmentioning
confidence: 99%